Economic aspects of the use of partial and full strength joints on multi-storey unbraced steel frames - Md. Tahir, Mahmood; Mohammad, Shahrin; Yahaya, Nordin; Saad, Sarifuddin; Abd. Rahman, Ahmad Baharuddin (Universiti Teknologi Malaysia, 2006)
Connections are usually designed as pinned or rigid although the actual behaviour is known to fall between these two extreme cases. The use of partial strength or semi-rigid connections has been encouraged by codes and studies on the matter known as semi-continuous construction have proven that substantial savings in steel weight of the overall construction. The objective of this research is to develop a series of standardized partial strength connections tables of flush end-plate connections and extended end plate for unbraced steel frames with the use of trapezoidal web profiled steel (TWP) sections. The range of standard connections presented in tabulated form is limited to fourteen tables comprised of different geometrical aspects of the connections. The moment capacity, shear capacity, geometrical aspects of the connections, the size of beams, and columns that are suitable with the connections are included in the standardized tables. A method proposed by Steel Construction Institute(SCI) which take into account the requirements in Eurocode 3 and BS 5950:2000 Part 1 were adopted to predict the moment capacity and shear capacity in developing the tables. Although the use of the proposed method is intended for hot rolled section, it has been proven via experimental tests that to apply the same proposed method to TWP section, provided that the predicted failure modes should comply with the requirements of Eurocode 3 and BS 5950:2000 Part 1. The TWP section should at least classified as compact section. The moment capacity and shear capacity in the standard tables presented in this report showed good agreement with the requirement of Eurocode 3 and BS 5950:2000 Part 1.